Nusyuz dalam Hukum Islam: Aspek Hukum dan Dampaknya Pada Hubungan Suami-Istri - Oming Ratna Wijaya; Chadziqatun Nafi'ah (MASADIR: Jurnal Hukum Islam, 2024)
This study analyzes the concept of nusyuz in Islamic law, focusing on the legal aspects, rights, and obligations as well as its impact on husband-wife relationships in Muslim societies. Nusyuz, which refers to the defiance of one of the parties in a marriage - either the husband or the wife - has significant implications for marital dynamics. This research discusses the Islamic legal provisions governing nusyuz, including its definition, causes, as well as the conflict resolution procedures stipulated by sharia. In addition, it explores the rights and obligations of husbands and wives in situations of nusyuz, as well as the impact this has on their relationship, both legally and emotionally. Based on a literature review and analysis of Islamic jurisprudence, this study found that Islamic law provides clear guidelines in dealing with nusyuz cases, with the aim of maintaining a balance of rights and obligations between husband and wife, as well as minimizing the negative impact on household harmony. However, in its application, there are various challenges, especially related to the interpretation and enforcement of the law which may differ in various Muslim societies. This research suggests a more adaptive and contextual approach in addressing nusyuz, to ensure that solutions are taken in accordance with the principles of justice and family welfare. Thus, it is hoped that this research can contribute to a deeper understanding of nusyuz and its implications in Islamic marital law.